Shunt MEMS switch requirements for Tunable Matching Network at 1.9 GHz in composite substrates - Silva Cortes, Victor Arturo; Fischer, Georg (German Microwave Conference (GeMiC), 2015)
A theoretical approach for the specification of shunt MEMS switches suitable for Tunable Matching Networks (TMN) at 1.9GHz is presented. DC-contact fixed-fixed beam MEMS switches designed with series metal-insulator-metal (MIM) capacitors at the grounding plane of a CPW transmission line provide the basic design block for the TMN. In the down-state, the MEMS switch makes an ohmic contact with the transmission line, as consequence, the down-state capacitance of the switch is dominated by the MIM capacitors. The proper dimensioning of the MIM capacitors enables to directly increase the capacitance ratio of the switch in order to operate at frequencies below 10 GHz. Based on predefined CPW transmission line configurations on composite substrates, the optimization of the capacitance ratio of the MEMS switch can be directly related to the geometry of the CPW transmission line.
elib2cris::1512001600,silva2015
Keywords: RF MEMS